Mechanized Qu-making may contribute to lactic acid bacteria overproliferation in Hongqu rice wine brewing: Insights into microbial dysbiosis and flavor quality deterioration - Hao Wang; Zihua Liang; Weiling Guo; Li Ni; Xucong Lv (International Journal of Food Microbiology, 2026)

Upcycling lignocellulosic biomass using a radial-axial fixed-bed ex-situ catalytic pyrolysis reactor - Fuzheng Li; Jinping Guo; Xingshan Shi; Weiling Piao; Cristina Franch; Yanping Chen; K. Seshan; Songbo He (Bioresource Technology, 2026)

Flexural behavior and progressive interfacial debonding mechanism of BFRP-PCM composite-strengthened tunnel segments - Cong Tian; Linchong Huang; Yu Liang; Weiling Gao; Chenghao Li (Tunnelling and Underground Space Technology, 2026)

Corrigendum to “CaWRKY8 participates in the defense response of pepper to pepper mild mottle virus by negatively regulating the expression of defense-related genes” [Plant Sci. 370 (September) (2026) 113227] - Xiaohui Zhan; Ning Li; Zhanfeng Song; Yuanyuan Mao; Kai Xu; Xiaodi Wang; Shenghua Gao; Yanxu Yin; Weiling Yuan; Weifang Chen; Mengyi Li; Minghua Yao; et al. (Plant Science, 2026)

CaWRKY8 participates in the defense response of pepper to pepper mild mottle virus by negatively regulating the expression of defense-related genes - Xiaohui Zhan; Ning Li; Zhanfeng Song; Yuanyuan Mao; Kai Xu; Xiaodi Wang; Shenghua Gao; Yanxu Yin; Weiling Yuan; Weifang Chen; Mengyi Li; Minghua Yao; et al. (Plant Science, 2026)

Intestinal Microbiomics and Liver Metabolomics Insights into the Improvement Effects of Lactiplantibacillus plantarum FJG2627 on Lipopolysaccharide-Induced Acute Liver Injury in Mice - Siyu He; Yuheng Yang; Li Ni; Xucong Lv; Weiling Guo; Zhifeng Cai; Youting Chen (Probiotics and Antimicrobial Proteins, 2026)

Grazing thresholds based on mean Net Primary Productivity (NPP) and NPP trends support region-specific grazing management in Xinjiang grasslands - Jiaxin Li; Wenwu Zhao; Jingyi Ding; Weiling Niu; Yiyin Liu; Weiwei Zhu; Paulo Pereira (Journal of Environmental Management, 2026)

Biochar-driven cycling of Fe(II)/Fe(III) and Co(II)/Co(III) in cobalt ferrite for efficient norfloxacin degradation via Fenton-like pathway - Rui Gan; Fanguang Kong; Xiao Zhao; Daoqing Liu; Shuo Zhang; Wen Liu; Si Li; Weiling Sun (Chemical Engineering Journal, 2026)

Carrier-free nanoparticles derived from Huanglian Jiedu decoction target ATP5F1C to eliminate senescent cells and ameliorate pulmonary fibrosis - Ying Zhang; Lirun Zhou; Yajian Li; Weiling Wang; Tong Yang; Qianyu Zhang; Hechen Tang; Jiayun Guo; Ling Huang; Chen Wang; Zheng Chu; Ang Ma; et al. (Chemical Engineering Journal, 2026)

Explainability and privacy in AI-enabled crop monitoring: Trends and future directions in soybean research - Jayme Garcia Arnal Barbedo; Marcelo Santos da Silva; Mirela Teixeira Cazzolato; Lucas Pascotti Valem; Renato Tinós; Roseli Aparecida Francelin Romero; Luiz Otavio Murta; Adriano de Jesus Holanda; Joaquim Cezar Felipe; José Baldin Pinheiro; José Tiago Barroso Chagas; Roberto Fray da Silva; et al. (Computers and Electronics in Agriculture, 2026)

Nontarget screening uncovers the overlooked impact of antibiotic transformation products on riverine resistomes - Yiming Feng; Xuman Zhang; Shanshan Lai; Fan Chen; Jingrun Hu; Min Li; Weiling Sun (Journal of Hazardous Materials, 2026)

Lacticaseibacillus rhamnosus FJG1530 modulate gut microbiota and liver metabolism to alleviate lipopolysaccharide-induced acute liver injury in mice - Siyu He; Weiling Guo; Yuheng Yang; Li Ni; Xucong Lv; Youting Chen (Food Bioscience, 2026)

Side-deep placement of controlled-release urea combined with alternate wetting and drying irrigation achieves sustainable intensification of rice production in the rice–wheat system - Yuan Wang; Li Zhang; Kai Ming; Lin Cao; Song Guo; Jiaming Lu; Ziwei Li; Weiling Wang; Can Zhao; Fengping Yang; Ke Xu; Hongcheng Zhang; et al. (Field Crops Research, 2026)

Involvement of the PINK1/Parkin signaling pathway in 4-vinylcyclohexene diepoxide-induced ovary toxicity in rats - Yue Che; Xiaozhu Wang; Qian Li; Xiyi Peng; Zhen Liu; Wenhui Xu; Mei Jiang; Ting Wang; Jian Gao; Weiling Wang (Food and Chemical Toxicology, 2025)

Mediating Zn loading on Cu-Zn bimetallic catalyst for electrochemical CO2 reduction into tunable syngas - Yafei Guo; Yangna Luo; Hanlin Wang; Xianglin Chen; Xiang Liu; Benshuai Guo; Jian Sun; Ruilin Wang; Weiling Li; Chuanwen Zhao (Fuel, 2025)

Better inversion of rice nitrogen nutrition index at early panicle initiation stage using spectral features, texture features, and wavelet features based on UAV multispectral imagery - Ziwei Li; Yuliang Zhang; Jiaming Lu; Yuan Wang; Can Zhao; Weiling Wang; Jianjun Wang; Hongcheng Zhang; Zhongyang Huo (European Journal of Agronomy, 2025)

Unveiling the mechanism and driving factors of pharmaceutical and personal care product (PPCP) removal in wastewater treatment plants - Shaoyang Li; Zhen Gao; Tianyi Chen; Zhile Pan; Dianbao Li; Yanran Dong; Junjie Li; Yanli Zhang; Sihan Cui; Weiling Sun; Nan Xu (Journal of Environmental Management, 2025)

In-situ monitoring of soil water characteristics using plant microbial fuel cell: Implications on slope stability analyses - Liye Li; Boneng Chen; Weiling Cai; Ankit Garg (Ecological Engineering, 2025)

Multiphysics simulation of frost heave in unsaturated road systems under covering effect - Lin Li; Zepeng Zhang; Weiling Zu; Panpan Li; Weibing Gong (Transportation Geotechnics, 2025)

Association between low-dose ionizing radiation and hypertension: a cohort study in China - Beining Wu; Lin Song; Lan Lin; Jin Wang; Lejia Zhu; Weiling Chan; Geyang Li; Li Zhou; Zhongying Xu; Jing Xiao; Yulong Lian (International Archives of Occupational and Environmental Health, 2025)

High-accuracy velocity analysis for multiple AVO seismic data - Yankai Xu; Jiawei Li; Jiao Qi; Siyuan Cao; Hongwei Liu; Weiling Li; Hongduo Zhu (Acta Geophysica, 2025)

Metagenomics reveals the differences in flavor quality of rice wines with Hongqu and Maiqu as the fermentation starters - Siwen Hou; Zihua Liang; Qi Wu; Qiqi Cai; Qibiao Weng; Weiling Guo; Li Ni; Xucong Lv (Food Microbiology, 2025)

A novel highly efficient co-catalyst for enhancement of photocatalytic hydrogen production activity and stability of Cd0.5Zn0.5S: Silicotungstic acid nanoparticles embedded with NiOx clusters - Jiwei Zhang; Weiling Nie; Lixia Qin; Taiyang Zhang; Xiangqing Li; Shi-Zhao Kang (Journal of Environmental Chemical Engineering, 2024)

Deciphering heart failure: an integrated proteomic and transcriptomic approach with experimental validation - Jun Cao; Zhaohai Su; Bilong Zhang; Jiangyong Yang; Yueting Wang; Ling Huang; Gang Cao; Hui Xie; Xiutong Zhong; Hengqing Zhu; Rengui Jiang; Tian Li; et al. (Functional & Integrative Genomics, 2024)

Methylotrophic substrates stimulated higher methane production than competitive substrates in mangrove sediments - Weiling Dong; Jinjie Zhou; Cui-Jing Zhang; Qin Yang; Meng Li (Science of The Total Environment, 2024)

Biochar application for enhancing water and nitrogen use efficiency of understory acacia species in a suburban native forest subjected to nitrogen deposition in Southeast Queensland - Weiling Sun; Yinan Li; Zhihong Xu; Yifan Bai; Shahla Hosseini Bai (Plant and Soil, 2024)
Purpose The fuel reduction prescribed burning and biochar application can have significant impacts on water and nitrogen (N) use efficiency of understory acacia species as well as soil carbon (C) and N pools in a suburban native forest subject to N deposition in Southeast Queensland, Australia. Methods We evaluated the impact of biochar application rates (0, 5.0 and 10.0 t biochar per hectare) and prescribed burning on soil-plant interactions in carbon (C) and N cycling in a suburban native forest in the first two years of biochar application or three and half years of the recently prescribed burning. Results Anthropogenic N deposition not only enhanced N losses caused by N leaching and denitrification, but also inhibited biological N fixation (BNF) by increasing N availability in forest systems. The Acacia leiocalyx with higher water use efficiency was more inclined to utilize easily available N resources (from N deposition), compared with A. disparismma . In this study, biochar application could indeed reduce N loss in forest soil and improve soil fertility by improving plant water and N use efficiency. Meanwhile, soil moisture content affected by biochar application also influenced soil N transformations by affecting soil microbial activity. Conclusion For urban forest soils, the high N availability caused by N deposition could inhibit the BNF in a suburban native forest ecosystem. The high-porosity physical structure of biochar applied increased the soil water content and soil N retention capacity.

Distribution and drivers of co−hosts of antibiotic and metal(loid) resistance genes in the fresh−brackish−saline groundwater - Xuming Xu; Huan Chen; Lei Du; Chunfang Deng; Ruoqi Ma; Bin Li; Jiarui Li; Shufeng Liu; Raghupathy Karthikeyan; Qian Chen; Weiling Sun (Chemosphere, 2024)

Intelligent operation-activated dual light-up nanointerrogator for on-site high-performance bioimaging - Tiantian Li; Yingying Li; Die Hu; Yu Luo; Weiling Song; Peng He; Jing-Juan Xu; Hong Zhou (Chemical Engineering Journal, 2024)

Impacts of rapidly urbanizing watershed comprehensive management on per- and polyfluoroalkyl substances pollution: Based on PFAS “diversity” assessment - Nan Xu; Zhile Pan; Wenjing Guo; Shaoyang Li; Dianbao Li; Yanran Dong; Weiling Sun (Water Research, 2024)

Profiles, drivers, and prioritization of antibiotics in China’s major rivers - Yi Liu; Meng Zhang; Yang Wu; Si Li; Jingrun Hu; Weiling Sun; Jinren Ni (Journal of Hazardous Materials, 2024)

When antibiotics encounter microplastics in aquatic environments: Interaction, combined toxicity, and risk assessments - Yibo Zhang; Xin Xu; Jing Xu; Zhang Li; Long Cheng; Jie Fu; Weiling Sun; Chenyuan Dang (Science of The Total Environment, 2024)

Industry chain and challenges of microalgal food industry-a review - Yuanhao Chen; Honghao Liang; Hong Du; Valentina Jesumani; Weiling He; Kit-Leong Cheong; Tangcheng Li; Ting Hong (Critical Reviews in Food Science and Nutrition, 2024)

Designing regional joint prevention and control schemes of PM2.5 based on source apportionment of chemical transport model: A case study of a heavy pollution episode - Yangjun Wang; Miao Ning; Qingfang Su; Lijuan Wang; Sen Jiang; Yueyi Feng; Weiling Wu; Qian Tang; Shiyu Hou; Jinting Bian; Ling Huang; Guibin Lu; et al. (Journal of Cleaner Production, 2024)

Promotional role of Ni photodepositing on Ru confined TiO2 nanotubes catalyzed CO2 methanation - Peiwei Han; Jun Zhang; Weiling Zhang; Zizhen Niu; Guowei Wang; Xiangnan Li; Juan Li; Nan Wang; Xiaoman Wang; Huangzhao Wei; Yong Chen; Xinjun Li (Chemical Engineering Journal, 2024)

Long-term effects of biochar application on biological nitrogen fixation of acacia species and soil carbon and nitrogen pools in an Australian subtropical native forest - Yinan Li; Weiling Sun; Zhihong Xu; Yifan Bai; Shahla Hosseini Bai (Journal of Soils and Sediments, 2024)
Purpose Biological nitrogen (N) fixation (BNF) of understory acacia species presents a potential way for effectively restoring N in forest systems. This study aimed to quantify the impact of acacia species and biochar application rates on BNF and soil mineral N in a suburban native forest of subtropical Australia in the first 4–5 years after prescribed burning. Method Plant growth values and BNF were measured to assess the impact of biochar rates at 0, 5, and 10 t ha −1 on different acacia species. Soil NH 4 + -N and NO 3 − -N along with their N isotope composition (δ 15 N) were determined to investigate soil–plant interactions in response to acacia species and biochar application. Results The application of 10 t ha −1 biochar significantly enhanced the growth of acacia species, and concurrently reduced the loss of NO 3 − -N at soil depths of 0–5 and 5–10 cm. Compared with Acacia disparimma (percentage of N derived from the atmosphere or %Ndfa: 78.2%), A. leiocalyx demonstrated significant higher BNF ability (%Ndfa: 91.3%). Similarly, A. leiocalyx had better growth, in terms of height (269.1 cm versus 179.6 cm), diameter at ground level (2.62 cm versus 1.94 cm), basal area (6.49 cm 2 versus 3.43 cm 2 ) and volume (692.2 cm 3 versus 258.0 cm 3 ). This was associated with its ability to promote organic matter mineralization, resulting in the accumulation of 15 N-depleted NH 4 + -N. NH 4 + -N, acting as a substrate, was transformed into NO 3 − -N through nitrification. From regression analysis, the efficient absorption of NH 4 + -N by A. leiocalyx significantly mitigated NH 4 + -N leaching with increasing soil moisture concentration (SMC), resulting in lower δ 15 N of NH 4 + -N, which was more negatively related to SMC (R 2 = 0.401), compared to that of A. disparimma (R 2 = 0.250) at soil depth of 0–5 cm. The production of NO 3 − -N was reduced, leading to lower NO 3 − -N concentrations of A. leiocalyx than A. disparimma at soil depth of 0–5 cm (8.06 µg N g −1 versus 9.61 µg N g −1 ) and that of 5–10 cm (8.24 µg N g −1 versus 9.21 µg N g −1 ) respectively. Conclusions As an effective soil amendment, biochar exhibited promise in reducing mineral N loss and stimulating plant growth in long-term applications of exceeding three years. Higher BNF capacity and greater plant growth were observed with A. leiocalyx , compared with those of A. disparimma . The retention and utilisation of mineral N by A. leiocalyx can be considered as strategy to restore forest soils.

Mxene hybrid conductive hydrogels with mechanical flexibility, frost-resistance, photothermoelectric conversion characteristics and their multiple applications in sensing - Mengjuan Hou; Maolin Yu; Weiling Liu; Hongyi Zhang; Zengsheng Wang; Jingjing Du; Lijian Xu; Na Li; Jianxiong Xu (Chemical Engineering Journal, 2024)

Highly efficient dehydration of polyols: In-situ Brønsted acid from boron phosphate catalyst - Chenxin Su; Shouquan Zhou; Shaoyun Wu; Mingbin Gao; Weiling Zhang; Zhuang Ma; Longfei Yan; Fuweng Zhang; Jingjing Chen; Haohong Li; Jie Liu; Huidong Zheng (Chemical Engineering Journal, 2024)

Association between occupational noise and obesity: a retrospective cohort study in China - Geyang Li; Weile Wu; Li Zhou; Weiling Chan; Jin Wang; Lejia Zhu; Lin Song; Lan Lin; Beining Wu; Jing Xiao; Yulong Lian (International Archives of Occupational and Environmental Health, 2024)

Bioelectricity generation in plant microbial fuel cells: Influence of vegetation density and unsaturated soil properties - Boneng Chen; Liye Li; Weiling Cai; Ankit Garg (Biomass and Bioenergy, 2024)

Accurate Shortwave Radiation Simulation with a Two-Layer Aerosol Model in Xinjiang Region - Guan Huang; Yonghang Chen; Qiong Liu; Pengtao Wang; Qianshan He; Qing He; Shuai Li; Weiling Shao; Ting Fan (Journal of Meteorological Research, 2024)

Relationship between exposure to metalworking fluids and nonalcoholic fatty liver disease - Weiling Chan; Geyang Li; Li Zhou; Jin Wang; Lin Song; Lejia Zhu; Lan Lin; Beining Wu; Jing Xiao; Yulong Lian (International Archives of Occupational and Environmental Health, 2024)

Content analysis and drug safety evaluation of four furanocoumarins in six pomelos produced in China - Weiling Chen; Zeqi Li; Yujiao Cheng; Guijie Li; Jiaqi Li; Linhua Huang; Qiuming Gu; Houjiu Wu (Natural Product Research, 2023)

Rapid and noninvasive cell assay by microfluidic-integrated intracavity evanescent field absorption in a fiber ring laser - Jia Shi; Ziyi Xu; Ke Yang; Xianguo Li; Cuijuan Guo; Hua Bai; Weiling Fu; Pingjuan Niu; Jianquan Yao; Xiang Yang (Analytica Chimica Acta, 2023)

Public–private partnerships and carbon reduction targets: evidence from PPP investments in energy and environmental protection in China - Xinshuo Hou; Weiling Li; Dongyang Li; Jianghuan Peng (Environment, Development and Sustainability, 2023)

Short-term changes in soil labile carbon and nitrogen pools with biochar application in a suburban native forest in subtropical Australia - Jiaping Yang; Juan Zhan; Sabah Taresh; Weiling Sun; Yinan Li; Ashrafun Nessa; Qinggui Wu; Zhihong Xu (Journal of Soils and Sediments, 2023)

Wastewater treatment plant effluents exert different impacts on antibiotic resistome in water and sediment of the receiving river: Metagenomic analysis and risk assessment - Yang Wu; Si Li; Ke Yu; Jingrun Hu; Qian Chen; Weiling Sun (Journal of Hazardous Materials, 2023)

Active compounds and potential targets of Shuganning injection in the treatment of hepatocellular carcinoma by network pharmacology and in vitro validation - Xiao Han; Jiayan Huang; Jia Lu; Feng He; Fang Wang; Shuangfeng Li; Hao Zhong; Haiyang Yu; Weiling Pu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Animal production predominantly contributes to antibiotic profiles in the Yangtze River - Jingrun Hu; Si Li; Wei Zhang; Damian E. Helbling; Nan Xu; Weiling Sun; Jinren Ni (Water Research, 2023)

Insights into the driving factors of vertical distribution of antibiotic resistance genes in long-term fertilized soils - Ying Li; Fanguang Kong; Si Li; Jie Wang; Jingrun Hu; Shuo Chen; Qing Chen; Yanming Li; Xuejiao Ha; Weiling Sun (Journal of Hazardous Materials, 2023)

Deciphering the dynamics of metal and antibiotic resistome profiles under different metal(loid) contamination levels - Pinggui Cai; Qian Chen; Wenran Du; Shanqing Yang; Jiarui Li; Hetong Cai; Xiaohui Zhao; Weiling Sun; Nan Xu; Jiawen Wang (Journal of Hazardous Materials, 2023)

Correlation of heavy metals’ exposure with the prevalence of coronary heart disease among US adults: findings of the US NHANES from 2003 to 2018 - Xi Li; Dongdong Zhang; Yang Zhao; Lei Kuang; Hao Huang; Weiling Chen; Xueru Fu; Yuying Wu; Tianze Li; Jinli Zhang; Lijun Yuan; Huifang Hu; et al. (Environmental Geochemistry and Health, 2023)

Enhancing biosensing with fourfold amplification and self-powering capabilities: MoS2@C hollow nanorods-mediated DNA hexahedral framework architecture for amol-level liver cancer tumor marker detection - Jinyue Shi; Weiling Qin; Yu Lin; Mingxiang Li; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Hormesis effects of sulfoxaflor on Aphis gossypii feeding, growth, reproduction behaviour and the related mechanisms - Li Wang; Junshu Zhu; Qinqin Wang; Xuejiao Ji; Wenjie Wang; Weiling Huang; Changhui Rui; Li Cui (Science of The Total Environment, 2023)

Air pollution exposure and heart failure: A systematic review and meta-analysis - Dongdong Zhang; Weiling Chen; Cheng Cheng; Hao Huang; Xi Li; Pei Qin; Chuanqi Chen; Xinping Luo; Ming Zhang; Jing Li; Xizhuo Sun; Yu Liu; et al. (Science of The Total Environment, 2023)

Reveal the major factors controlling quinolone adsorption on mesoporous carbon: Batch experiment, DFT calculation, MD simulation, and machine learning modeling - Hongjun Zhao; Yitao Lyu; Jingrun Hu; Min Li; Huan Chen; Yi Jiang; Moran Tang; Yang Wu; Weiling Sun (Chemical Engineering Journal, 2023)

Integration of target, suspect, and nontarget screening with risk modeling for per- and polyfluoroalkyl substances prioritization in surface waters - Jingrun Hu; Yitao Lyu; Huan Chen; Leilei Cai; Jie Li; Xiaoqiang Cao; Weiling Sun (Water Research, 2023)

circTAB2 inhibits lung cancer proliferation, migration and invasion by sponging miR-3142 to upregulate GLIS2 - Weiling Man; Yumeng Cui; Jie Li; Yanghua Li; Jie Jin; Yang Jin; Xiaojie Wu; Rongbin Zhong; Xiang Li; He Yao; Yanli Lin; Lihe Jiang; et al. (Apoptosis, 2023)

Exploring diversity patterns and driving mechanisms of the antibiotic resistome and microbiome in saline groundwater - Moran Tang; Qian Chen; Haohui Zhong; Feng Ju; Yang Wu; Jingrun Hu; Si Li; Weiling Sun (Journal of Hazardous Materials, 2023)

Exosome proteomics study of the effects of traditional cigarettes and electronic cigarettes on human bronchial epithelial cells - Weiling Wang; Rong Zeng; Min Liu; Mulan Chen; Shiqin Wei; Bowen Li; Suhong Yu (Toxicology in Vitro, 2023)

Development of an interpretable machine learning model associated with heavy metals’ exposure to identify coronary heart disease among US adults via SHAP: Findings of the US NHANES from 2003 to 2018 - Xi Li; Yang Zhao; Dongdong Zhang; Lei Kuang; Hao Huang; Weiling Chen; Xueru Fu; Yuying Wu; Tianze Li; Jinli Zhang; Lijun Yuan; Huifang Hu; et al. (Chemosphere, 2023)

Environmental DNA metabarcoding reveals the impacts of anthropogenic pollution on multitrophic aquatic communities across an urban river of western China - Xuming Xu; Yibin Yuan; Zhaoli Wang; Tong Zheng; Hetong Cai; Malan Yi; Tianhong Li; Zhijie Zhao; Qian Chen; Weiling Sun (Environmental Research, 2023)

Pollution heaven or pollution halo? Assessing the role of heterogeneous environmental regulation in the impact of foreign direct investment on green economic efficiency - Hui Zheng; Li Zhang; Weiling Song; Hairong Mu (Environmental Science and Pollution Research, 2022)

Sulfoxaflor resistance in Aphis gossypii: resistance mechanism, feeding behavior and life history changes - Li Wang; Li Cui; Qinqin Wang; Yanpeng Chang; Weiling Huang; Changhui Rui (Journal of Pest Science, 2022)

Roots and microbiome jointly drive the distributions of 17 phytohormones in the plant soil continuum in a phytohormone‐specific manner - Yuqiu Lu; Enzhao Wang; Zhiyu Tang; Junpeng Rui; Yanling Li; Zhixi Tang; Weiling Dong; Xiongduo Liu; Timothy S. George; Alin Song; Fenliang Fan (Plant and Soil, 2022)

miR-455-5p regulates atrial fibrillation by targeting suppressor of cytokines signaling 3 - Weiling Li; Na Qi; Shuo Wang; Wenyan Jiang; Tao Liu (Journal of Physiology and Biochemistry, 2021)

Polybrominated diphenyl ethers (PBDEs) in the Danjiangkou Reservoir, China: identification of priority PBDE congeners - Yaomin Luo; Wanzi Shi; Mingtao You; Ruijie Zhang; Si Li; Nan Xu; Weiling Sun (Environmental Science and Pollution Research, 2021)

Characterization and genome analysis of Klebsiella phage P509, with lytic activity against clinical carbapenem-resistant Klebsiella pneumoniae of the KL64 capsular type - Min Li; Yuyi Xiao; Pei Li; Zitong Wang; Weiling Qi; Zitai Qi; Liang Chen; Hong Du; Wei Zhang (Archives of Virology, 2020)

Additional application of aluminum sulfate with different fertilizers ameliorates saline-sodic soil of Songnen Plain in Northeast China - Meng Zhou; Xiaobing Liu; Qingfeng Meng; Xiannan Zeng; Jizhou Zhang; Dawei Li; Jie Wang; Weiling Du; Xianfa Ma (Journal of Soils and Sediments, 2019)

Alleviation of atrazine toxicity to maize seedlings grown in soils with amendment of biochar derived from wheat under different temperatures - Yifan Wang; Yi Tang; Qun Jiang; Xinyuan Zhang; Weiling Xie; Ruizhen Li; Wenzhu Liu; Jiaming Kang; Ying Zhang (Environmental Science and Pollution Research, 2019)

Occurrence and distribution of antibiotic resistance genes in the sediments of drinking water sources, urban rivers, and coastal areas in Zhuhai, China - Aolin Li; Lujun Chen; Yan Zhang; Yile Tao; Hui Xie; Si Li; Weiling Sun; Jianguo Pan; Zhidong He; Chaoan Mai; Yingying Fan; Huanchao Xian; et al. (Environmental Science and Pollution Research, 2018)

Hyperspectral Image Compression and Reconstruction Based on Block-Sparse Dictionary Learning - Yanwen Chong; Weiling Zheng; Haonan Li; Zhixi Qiao; Shaoming Pan (Journal of the Indian Society of Remote Sensing, 2018)

Distribution and risk assessment of trace metals in sediments from Yangtze River estuary and Hangzhou Bay, China - Feipeng Li; Lingchen Mao; Yubao Jia; Zhujun Gu; Weiling Shi; Ling Chen; Hua Ye (Environmental Science and Pollution Research, 2018)

Serum Protein-Based Profiles as Novel Biomarkers for the Diagnosis of Alzheimer’s Disease - Shu Yu; Yue-Ping Liu; Hai-Liang Liu; Jie Li; Yang Xiang; Yu-Hui Liu; Shu-Sheng Jiao; Lu Liu; Yajiang Wang; Weiling Fu (Molecular Neurobiology, 2017)

Migration of endophytic diazotroph Azorhizobium caulinodans ORS571 inside wheat (Triticum aestivum L) and its effect on microRNAs - Li Qiu; Qiang Li; Junbiao Zhang; Yongchao Chen; Xiaojun Lin; Chao Sun; Weiling Wang; Huawei Liu; Baohong Zhang (Functional & Integrative Genomics, 2017)

Genome-wide identification, classification, and analysis of NADP-ME family members from 12 crucifer species - Peng Tao; Weiling Guo; Biyuan Li; Wuhong Wang; Zhichen Yue; Juanli Lei; Yanting Zhao; Xinmin Zhong (Molecular Genetics and Genomics, 2016)

Genome-wide identification and characterization of aquaporin genes (AQPs) in Chinese cabbage (Brassica rapa ssp. pekinensis) - Peng Tao; Xinmin Zhong; Biyuan Li; Wuhong Wang; Zhichen Yue; Juanli Lei; Weiling Guo; Xiaoyun Huang (Molecular Genetics and Genomics, 2014)

Changes in individual plant traits and biomass allocation in alpine meadow with elevation variation on the Qinghai-Tibetan Plateau - WeiLing Ma; PeiLi Shi; WenHua Li; YongTao He; XianZhou Zhang; ZhenXi Shen; SiYue Chai (Science China Life Sciences, 2010)

Nitrous Oxide Emissions from Wetland Rice–Duck Cultivation Systems in Southern China - Chengfang Li; Cougui Cao; Jingping Wang; Ming Zhan; Weiling Yuan; Shahrear Ahmad (Archives of Environmental Contamination and Toxicology, 2009)

Expression and purification of a soluble B lymphocyte stimulator mutant modified with the T-helper cell epitope - Huiguang Gao; Weiling Fu; Rongfen Li; Linfeng Chen; Qing Ji; Li Zhang; Gang Huang; Fengtian He (Biotechnology Letters, 2006)

The current situation and trend of tomato cultivation in China - Zhihao Xu; Weiling Shou; Kaimay Huang; Sengjiu Zhou; Guojing Li; Guangchao Tang; Xiuchu Xiu; Guangliang Xu; Baishen Jin (Acta Physiologiae Plantarum, 2000)

The determination of physiological race of Fusarium oxysporum f. sp. lycopersici of tomato in Zhejiang, China - Zhihao Xu; Kaimay Huang; Weiling Shou; Sengjiu Zhou; Guojing Li; Liping Chen; Zhihui Xu; Hongxia Wang; Xiuchu Xiu; Guangliang Xu; Baishen Jin (Acta Physiologiae Plantarum, 2000)